2000
DOI: 10.4315/0362-028x-63.9.1204
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Listeria monocytogenes Strains Show Enhanced Adherence to Food Contact Surface after Short Contact Times

Abstract: Adherence of 3 persistent and 14 nonpersistent Listeria monocytogenes strains to stainless steel surfaces after short and long contact times was investigated. L. monocytogenes strains were obtained from poultry plants and an ice cream plant throughout several years. Adherence tests were performed in tryptic soy broth at 25 degrees C for 1, 2, and 72 h. Test surfaces were rinsed after the contact time, and attached cells were stained with acridine orange and enumerated with an epifluorescence microscope. The pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
127
1
16

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(153 citation statements)
references
References 19 publications
9
127
1
16
Order By: Relevance
“…Flagella in L. monocytogenes are not believed to be an important virulence determinant for human disease (41,49). However, there is considerable interest in the mechanisms by which this organism colonizes the surfaces found throughout the food processing environment (4,7,19,23,31,47). Previous research has demonstrated that the organism can attach to the common surfaces used throughout the food processing environment (24,43) and may also form biofilms (7).…”
mentioning
confidence: 99%
“…Flagella in L. monocytogenes are not believed to be an important virulence determinant for human disease (41,49). However, there is considerable interest in the mechanisms by which this organism colonizes the surfaces found throughout the food processing environment (4,7,19,23,31,47). Previous research has demonstrated that the organism can attach to the common surfaces used throughout the food processing environment (24,43) and may also form biofilms (7).…”
mentioning
confidence: 99%
“…Because of the attached food particles, the mechanical cleaning of lines A and B was more difficult, which may have favored the persistence of L. monocytogenes. Furthermore, all environmental and equipment isolates of the plant belonged to either serotype 1/2a or 1/2c, both of which have shown increased biofilm formation compared with other serotypes (6,20), and hence, isolates of these serotypes may more often colonize surfaces and resist sanitizing agents. Because lines A and B were situated next to each other, it is also possible that inadequate washing procedures caused splashes, which spread the contamination to the adjacent line.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that the existence of pathogens as free-living or plankton-associated cells, is critical to their survival in the environment as well as their transmission from one host to another (Donlan and Costerton, 2002). Several studies have revealed the preponderance of Listeria species to exist as biofilms attached to surfaces such as stainless steel, glass and propylene (Mafu et al, 1990), and food and food processing environments (Lunden et al, 2000). There is however little or no report in the literature on Listerio-plankton association in the natural environment.…”
Section: Listeria Monocytogenes In the Human And Animal Environmentmentioning
confidence: 99%